Automated identification of maximal differential cell populations in flow cytometry data. Issue 2 (22nd October 2021) - Yue, Alice; Chauve, Cedric; Libbrecht, Maxwell W.; Brinkman, Ryan R.
Abstract: We introduce a new cell population score called SpecEnr (specific enrichment) and describe a method that discovers robust and accurate candidate biomarkers from flow cytometry data. Our approach identifies a new class of candidate biomarkers we define as driver cell populations, whose abundance is associated with a sample class (e.g., disease), but not as a result of a change in a related population. We show that the driver cell populations we find are also easily interpretable using a lattice‐based visualization tool. Our method is implemented in the R package flowGraph, freely available on GitHub (github.com/aya49/flowGraph ) and on BioConductor.